Focused microwave assisted extraction setup and extraction of sesamol from sesame seed - Sharma, Maya; Patel, Deep P; Meghwal, Kusum; Mitra, Jayeeta (Journal of Postharvest Technology, 2022)
Microwave-assisted extraction technique opens a new room for speeding up extraction of bioactive components from food matrix while  maximizing the yield recovery. In this study, a lab scale microwave assisted extraction system was fabricated which utilized focused  microwave radiation. Its major components were domestic microwave oven, extraction assembly, cooling assembly and peristaltic pump.  The system was used to extract sesamol from roasted sesame seed. Extraction was performed at different levels of microwave power (450,  600 and 800 W) and irradiation time (2, 4 and 6 min) with 20 ml concentrated ethyl acetate solvent. Analytical quantification was done using  liquid chromatography. Extraction yield was lower at 450 W for 2 min of irradiation exposure to the sample. Maximum yield was obtained at  800 W power for 6 min of microwave heating. MAE yield was compared with soxhlet extraction method which indicated two times more  recovery in case of MAE method.
Keywords: Focused microwave assisted extraction; soxhlet extraction; sesamol; sesame seed